2018
DOI: 10.23922/jarc.2018-011
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of neoadjuvant-synchronous S-1 plus radiotherapy for locally advanced rectal cancer: a multi-institutional prospective phase II study

Abstract: Objectives: This study aimed to evaluate the long-term outcomes of neoadjuvant chemoradiotherapy with S-1 in patients with locally advanced rectal cancer. Methods: A multi-institutional, prospective, phase II trial was conducted between April 2009 and August 2011. The study enrolled 37 patients with histologically proven rectal carcinoma (T3-4 N0-3 M0) who underwent neoadjuvant chemoradiotherapy with S-1. Total mesorectal excision with D3 lymphadenectomy was performed 4-8 weeks after completion of neoadjuvant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 24 publications
4
6
0
Order By: Relevance
“…S-1, a prodrug of 5-FU, is one of the candidates for this chemotherapy regimen in Japan. There are several reports on S-1 alone [ 20–25 ] and combined therapy with other chemotherapeutic agents [ 15–19 ] for preoperative CRT for LARC, but there are few reports showing the treatment outcomes of S-1 alone, especially with regard to long-term results [ 25 ]. Table 6 shows the results of CRT using S-1 alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S-1, a prodrug of 5-FU, is one of the candidates for this chemotherapy regimen in Japan. There are several reports on S-1 alone [ 20–25 ] and combined therapy with other chemotherapeutic agents [ 15–19 ] for preoperative CRT for LARC, but there are few reports showing the treatment outcomes of S-1 alone, especially with regard to long-term results [ 25 ]. Table 6 shows the results of CRT using S-1 alone.…”
Section: Discussionmentioning
confidence: 99%
“…S-1 alone could be a useful option for preoperative CRT for LARC. However, there are very few reports on the treatment outcomes of preoperative CRT with S-1 alone for LARC, especially regarding long-term results [ 25 ], and the number of patients in these studies was limited [ 20–25 ]. In this study, we retrospectively assessed the efficacy and tolerability of S-1 in preoperative CRT for LARC.…”
Section: Introductionmentioning
confidence: 99%
“…In a report by Hiratsuka et al [35] on long-term prognosis, the rates of local recurrence, lung metastasis, and liver metastasis were 13.5%, 16.2%, and 2.7%, respectively. In the present study, although the observation period was only 3 years, the recurrence after surgery was well controlled, with only three patients (11%) experiencing lung metastasis.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, we only examined the short-term results. Only one study from Hiratsuka et al (12) reported the long-term outcomes of CRT with S-1 for locally advanced rectal cancer, noting a 5-year disease-free survival and 5-year overall survival of 66.7 and 74.7%, respectively, for Stage II and III rectal cancer. Therefore, further studies will be needed to confirm the efficacy of preoperative CRT with S-1 for locally advanced rectal cancer, including an assessment of the long-term outcomes regarding disease free survival and local recurrence, and sexual and urinary function.…”
Section: Discussionmentioning
confidence: 99%
“…S-1 contains not only tegafur as a radiosensitizer but also gimeracil, which enhances the efficacy of the radiotherapy (7)(8)(9). However, few studies regarding preoperative CRT with S-1 for rectal cancer have been conducted thus far (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%